Improved Charge Carrier Transport Across Grain Boundaries in N‐type PbSe by Dopant Segregation - Huaide Zhang; Minghao Shen; Christian Stenz; Christian Teichrib; Riga Wu; Lisa Schäfer; Nan Lin; Yiming Zhou; Chongjian Zhou; Oana Cojocaru‐Mirédin; Matthias Wuttig; Yuan Yu (Small Science)
Doping is an important and routine method to tune the properties of semiconductors. Dopants accumulated at grain boundaries (GBs) can exert a profound influence on microstructures and transport properties of heat and charge. To unravel the effect of dopant accumulation at GBs on the scattering of electrons, individual high‐angle GBs in three PbSe samples doped with different amounts of Cu using a home‐designed correlative characterization platform combining electron backscatter diffraction, microcircuit transport property measurements, and atom probe tomography are studied. The findings reveal that the segregation of Cu dopants to GBs reduces the GB potential barrier height. Once the GB phase reaches an equilibrium with saturated Cu, the extra Cu dopants distribute homogeneously inside the grains, compensating for vacancies and improving the electrical conductivity of the PbSe grains. The results correlate the Cu distribution at GBs and grains with local electrical properties, enlightening strategies for manipulating advanced functional materials by GB segregation engineering.